A Clinical and Genetic Review of Aniridia - Reza Jafari; Ahmad Ahmadzadeh Amiri (Mazandaran University of Medical Sciences, 2015)
Aniridia is a congenital pan-ocular, bilateral disorder. The term aniridia is a misleading misnomer, since at least a rudimentary iris is always present. Varied forms range from almost total absence to only mild hypoplasia of the iris. It is inherent in a number of syndromes, including Wilms tumor Aniridia-Genital anomalies-retardation (WAGR). Aniridia has been shown to be associated with mutations in the PAX6 gene, located on chromosome 11p13, telomeric to the Wilms' tumor predisposition gene (WT1). The pair box gene 6 (PAX6) situated at 11p13 has been confirmed to be the leading gene associated with aniridia. The PAX6 mutation is present in individuals worldwide and has been studied in Indian, Malaysian, Chinese and Mexican families. Several categories of PAX6 mutations include: nonsense mutations, splicing mutations, frameshift mutations (deletion or insertion), in-frame insertion or deletion, missense mutations and run-on mutations. A novel de novo frameshift mutation in PAX6 most possibly occurred in the paternal gamete. Mutation in PAX6 brings about amino acid substitution for instance proline to glutamine. Deletion of 11p13 involves the PAX6 (aniridia) locus and the adjacent WT1 (Wilms tumor) locus. Haploinsufficiency at the PAX6 locus brings on aniridia, a pan-ocular eye condition characterized by iris hypoplasia and various other anterior and posterior eye defects, subtle hypogonadotropic hypogonadism and borderline Growth Hormone (GH) deficiency. Aniridia may also be affiliated with retinal tears and detachments. Electroretinograms (ERGs) done in aniridia illustrate definite retinal dysfunction. Other clinical aspects related to aniridia are ptosis with reduced levator function and anterior polar cataracts. The PAX6 gene mutation was also associated with early-onset diabetes mellitus and aniridia. Aniridia combined with zonular cataract and polydactyly was also described in a patient with Bardet-Biedl syndrome. Aniridia with sensorineural deafness (cochlear) and aplasia of the patella was also reported; an autosomal-dominant inheritance with 100% penetrance. The WAGR syndrome is associated with obesity. Because of all the associations with other diseases as mentioned above, ophthalmologists should pay more attention to aniridia as a sign of a systematic disease. As aniridia is a global disease and has been reported in all five continents and several countries with different ethnic groups, herein we reviewed this important disorder.